The Effect of Managerial Skills, Education Level, and the Role of Village Consultative Body toward the Performance of Village Head - Nurul Afifah; Dian Anita Nuswantara (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
Researchers choose to research in Kabupaten Bojonegoro, because there were cases of misappropriation of village funds by the village head and there were cases of villages budget reporting to the head of local government. This study aims to look at the factors that can improve the performance of village heads in village finances. There are three independent variables tested, namely managerial ability, level of education, and the role of the Village Consultative Body (BPD), while the dependent variable in this study is the performance of village financial management. This study took a setting in Kabupaten Bojonegoro by taking a sample of village heads in 6 (six) sub-districts that received the largest village funds. The type of data used in this study is primary data collected through distributing questionnaires to respondents. The distribution of the questionnaire was carried out by meet the village head directly at the village head’s office, attend the village head forum, and send the questionnaire link via Whatsapp media. They are 150 samples collected through the purposive sampling technique. The data analysis technique used multiple linear regression with the SPSS 23 application program. The test results showed that the managerial ability and the role of the BPD had a significant effect on the village head's performance, while the level of education did not affect the performance of the village head. Keywords: Managerial skills, Level of education, The role of BPD, Performance, Head of village